Emotional state of Bosnian refugee and immigrant children in Turkey - (:unkn) unknown (My University, 2002)
Objective: The main purpose of this study is to assess the emotional state of Bosnian refugee and immigrant children in Istanbul/Turkey and to compare the findings. Methods: The subjects were given the Croatian version of the Child Depression Inventory (CDI) and Zivcic's Mood Scale, which consisted of 4 subscales: joy, fear, sadness and anger. Their parents also completed a Mood Scale. A data questionnaire was used for the refugee sample to obtain information about the war experience. Results: Mean CDI and Mood Scale scores were not elevated for both groups and no statistically significant difference was found. Refugee sample reports displayed higher correlations than the immigrant sample. Conclusion: The results can be interpreted as the refugees have spent enough time to normalize their war related emotions. Intergroup factors are important in the refugee sample.
Keywords: Children; Refugee; Trauma; War